Mini Review: Circular RNAs as Potential Clinical Biomarkers for Disorders in the Central Nervous System - Lu, Dan; Xu, An-Ding (Frontiers in Genetics, 2016)
Circular RNAs (circRNAs) are a type of noncoding RNAs (ncRNAs), produced in eukaryotic cells during post-transcriptional processes. They are more stable than linear RNAs, and possess spatio-temporal properties. CircRNAs do not distribute equally in the neuronal compartments in the brain, but largely enriched in the synapses. These ncRNA species can be used as potential clinical biomarkers in complex disorders of the central nervous system (CNS), which is supported by recent findings. For example, ciRS-7 was found to be a natural microRNAs sponge for miRNA-7 and regulate Parkinson’s disease (PD)/ Alzheimer’s disease (AD)-related genes; circPAIP2 is an intron-retaining circRNA which upregulates memory-related parental genes PAIP2 to affect memory development through PABP reactivation. The quantity of circRNAs carry important messages, either when they are inside the cells, or in circulation, or in exosomes released from synaptoneurosomes and endothelial. In addition, small molecules such as microRNAs and microvesicles can pass through the blood-brain barrier (BBB) and get into blood. For clinical applications, the study population needs to be phenotypically well-defined. CircRNAs may be combined with other biomarkers and imaging tools to improve the diagnostic power.